Analisis Fundamental untuk Menilai Saham dengan Metode Valuasi Relatif terhadap Keputusan Investasi - Gunawan, Candra; Hapsari, Nesti (Penerbit Goodwood, 2023)
Purpose: The purpose of this study is to determine the condition of a food and beverage company's stock price in an undervalued (cheap) or overvalued (expensive) position so that it can make investment decisions. Research methodology: This research methodology uses a quantitative descriptive method. The sampling technique used was purposive sampling based on criteria. Then obtained eight research samples including CEKA, ICBP, INDF, MYOR, ROTI, SKLT, ULTJ, and DLTA. For data collection techniques in this study using the documentation method and data analysis was performed manually using Microsoft Excel. Results: The results of stock valuation using the PER, PBV and PSR methods on average show that the company is in overvalued condition, including ICBP, MYOR, ROTI, ULTJ, SKLT and DLTA shares, so a good investment decision is to sell. Meanwhile, shares of CEKA and INDF companies have an average calculated value of undervalued (cheap) so the right investment decision is to buy these shares. Limitations: This study only uses six financial ratio scales to see company performance and share valuation using only relative valuation methods such as PER, PBV and PSR. Contribution: This research can be a good reference source for investors in making investment decisions, especially those who want to invest their funds in stocks. In addition, the company is expected to be able to provide evaluation information on the company's financial performance. So it can bring potential investors to invest and gain loyalty to the company.